Analisis IT Service Management (ITSM) Layanan E-Learning Universitas Bina Darma Menggunakan Framework ITIL V3 - Dyah Ikhtiarti; Tata Sutabri (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
Bina Darma University uses E-Learning as a development of information and communication technology in the learning and teaching process without face-to-face (online). Information Technology Service Management (ITSM) is information technology service management, a method that can be used in managing e-learning information technology systems at Bina Darma University. The ITIL V3 framework, the method used in research that focuses on the service operation domain, aims to measure the level of maturity in e-learning conditions. Some of the sub-domains used are event management, incident management, request fulfillment, problem management, and access management. The results of the study on the event management variable maturity level 2.90, incident management variable maturity level 2.45, problem management variable maturity level 2.13, request fulfillment variable maturity level 2.24, access management variable maturity level 3.18. The overall average value of all variables with the results of the questionnaire obtained is 2.58, which is on a scale of 3 of 5 maturity levels, namely defined.